ERD plus as a solution for teaching and learning of database system course / Anis Salwani Abu Bakar, Noraini Desa and Hasliza A Rahim @ Abd. Rahman - Abu Bakar, Anis Salwani; Desa, Noraini; A Rahim @ Abd. Rahman, Hasliza (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Nowadays, the ‘chalk and talk’ learning approach has nearly been replaced by online teaching and learning methods all over the world. In two decades, the Internet has changed the teaching and learning paradigm resulting in better learning outcomes while combating the reduction of resources, especially in tertiary level education (Nguyen, 2015). The approach of online and blended learning has been embedded in order to improve the quality of teaching and learning accordance to the Malaysia Education Development Plan 2015-2025 (Higher Education) which focuses on online learning as an important component in higher education. The use of online modeling platform of ERD Plus has given the opportunity to students to learn by themselves at their preferred time. The study aims to focus on the effectiveness of using ERD Plus, a web-based modeling platform as a learning tool for topic Database Model in DEC40073 Database System course. 50 students from Electrical Engineering Department of Politeknik Sultan Haji Ahmad Shah, Kuantan Pahang who took DEC40073 Database System course during December 2019 session had been selected as respondents. The results of the study show the increasing marks of students' assessment after using the ERD Plus simulation in related topics showing that the experience they gained from the online modeling platform prepares them to answer the assessment question accurately.